EP1170 Development of a risk model for survival and recurrence in patients with vulvar squamous cell carcinoma. (1st November 2019) - Kortekaas, KE; Bastiaannet, E; van Doorn, HC; Goddijn, IF; Rogaar, HJ; de Vos van Steenwijk, PJ; Ewing, PC; Creutzberg, CL; Akdeniz, K; Nooij, LS; van der Burg, SH; Bosse, T; et al.
Abstract : Introduction/Background: Increasing evidence points to better prognosis for human papillomavirus (HPV)-positive vulvar squamous cell carcinoma (HPVposVSCC) compared to HPV-negative VSCC (HPVnegVSCC). The aims of this study were to evaluate the clinical significance of HPV and other prognostic factors in a large cohort with VSCC patients and to develop risk models for survival and recurrence. Methodology: Patients with primary VSCC, surgically treated with curative intent between 2000 and 2015 ( n =421) were included. HPV was determined by HPV-PCR and p16 immunohistochemistry. Overall survival (OS), relative survival (RS), and recurrence-free period (RFP) were determined in patients with HPVposVSCC and HPVnegVSCC. A risk model based on prognostic factors with significant impact on OS and RFP was designed to predict risk of death and shorter RFP. Data were internally validated using a bootstrap resampling procedure. Results: Patients with HPVnegVSCC had worse 5-year OS, RS, and RFP than those with HPVposVSCC (52%, 64%, and 46% vs 82%; p =0.001, 90%; p =0.010, and 82%; p <0.001, respectively. Independent prognostic factors for unfavorable OS were FIGO stage III, age ≥70 and tumor-positive resection margins, and for shorter RFP HPV status and age ≥70. Risk models for OS and RFP were developed in which patients were classified into low, intermediate and high-risk categories for death or recurrence (AUC were 0.77 and 0.73 for OS and RFP, respectively). According to this model, 5-year OS was 89%, for the low, 65% for the intermediate, and 29% for the high-risk groups. In HPVposVSCC, 70% and 100% of patients were classified as low-risk for death and recurrence, respectively, compared to 22% and 21% of HPVnegVSCC patients. Conclusion: The developed risk models contribute to better prediction of survival and recurrence in surgically-treated VSCC patients. They may aid trial design and encourage the selection of high-risk patients potentially benefitting from new therapies or intensified follow-up. Disclosure: Nothing to disclose